PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ONLINE DI E-COMMERCE SHOPEE PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Munthe, Marcelino Nathanael (UNIKA Santo Thomas, 2025)
The purpose of this study is to analyze the Influence of Product Quality, Price, and Promotion on Online Purchasing Decisions in Shopee E-Commerce on Students of the Faculty of Economics and Business, Santo Thomas Catholic University, Medan. The population in this study were all students at the Faculty of Economics and Business, Santo Thomas Catholic University, Medan, Management Study Program who used Shopee e-commerce in the last 3 months (February - April 2025) with a minimum online purchasing frequency of 1 time or more during the last 3 months, namely 211 respondents. The sampling technique in this study was the Non-probability Sampling technique with the determination of the number of research samples based on the Slovin formula approach so that a sample of 138 respondents was obtained. The data analysis technique used was multiple linear regression analysis with hypothesis testing using the t test and F test at = 5%, with first conducting validity, reliability and classical assumption tests. The results showed that product quality did not have a significant effect on online purchasing decisions. Price and promotion had a positive and significant effect on online purchasing decisions and the variables of product quality, price, and promotion together had a significant effect on online purchasing decisions. Variations in purchasing decisions can be explained by variations in product quality, price, and promotion, amounting to 63.4 percent, while the remaining 36.6% is explained by other variables outside this study